Sistem Kontrol PID pada Purwarupa Robot Pembawa Barang berbasis Line Follower menggunakan Algoritma Path Planning - Priyo Prasetyo; Rizal Maulana; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The transporter robot is one of the uses of wheeled robots to help activities in the industrial world. The use of robots carrying goods in the industrial world, especially in the logistics industry, is very much needed because robots can move and sort goods quickly and accurately and compete in warehouse automation to remain competitive and reduce costs. The design of the cargo carrier robot in this study will be based on a line follower robot that can read a Quick Response (QR) code. This system will be built using an Arduino Mega 2560 microcontroller as the main control with input coming from the gm66 sensor as a QR code reading contained in an object that is useful for determining the path planning chosen by the robot in deciding the direction to achieve the goal and the HYS301 line sensor as line detection on the track. This system uses PID control to stabilize the robot's motion when moving on a line and uses a path planning algorithm to determine the direction to be traversed by the robot. The test results on the gm66 sensor show that the ideal distance of sensor reading is at a minimum distance of 15cm, while the optimal reading distance for the HYS301 line sensor is at a distance of 3mm from the floor surface. The PID parameter values ​​obtained so the robot can move in a straight line are Kp = 3, Kd = 0.5, and Ki = 0.7. The time it takes to reach the rise time is around 0.2 seconds, and the time it takes to reach the settling time is 0.69 seconds. The path planning algorithm used is the same as the direction of the robot's motion when it is run. The accuracy results when using the first, second, and third path planning from the tests carried out have a value of 100% each.